Pressure dependence of fiber bragg grating inscribed in perfluorinated polymer fiber - Ishikawa, Ryo; Lee, Heeyoung; Lacraz, Amédéé; Theodosiou, Antreas; Kalli, Kyriacos; Mizuno, Yosuke; Nakamura, Kentaro (My University, 2017)
We investigate the hydrostatic pressure dependence of the Bragg wavelength of a fiber Bragg grating (FBG) inscribed in a perfluorinated graded-index (PFGI-) polymer optical fiber (POF) at 1550 nm. At 0.5 MPa, the Bragg wavelength increased with time and became almost constant 150 min later. Such a long time constant probably originates from the unique structure of the PFGI-POF, which has a thick overcladding around its core and cladding. The pressure-dependence coefficient without considering the time constant was estimated to be 1.3 nm/MPa; this is over five times the values of other types of POF-FBGs. This indicates that by removing the overcladding of the PFGI-POF, fast-response high-sensitivity pressure sensing will be feasible. Once the Bragg wavelength became constant at 0.5 MPa, the pressure-dependence coefficient of the Bragg wavelength was measured to be -0.13 nm/MPa, the absolute value of which was comparable with those of other POF-FBGs, but with an opposite sign.
Keywords: Fiber bragg gratings; Polymer optical fibers; Pressure sensing; Temporal variations